Analisis Pelanggaran Kode Etik Advokat Didalam Persidangan Terkait Penyalahgunaan Keterangan Palsu Oleh Klien - Jhody Pujaka; Faishal Nurallamsyah; Tetty Marlina Tarigan (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2023)
As a constitution based on Pancasila and the Constitution of the Republic of Indonesia 1945, Indonesia guarantees the equality of all people before the law (Equality before law). In the realization and declaration of legal principles in society, the roles and functions of lawyers as free, independent and important professions, apart from judicial and law enforcement agencies such as the police and prosecutors, are important. The purpose of this article is to explain how the implementation of the Code of Ethics is sanctioned against lawyers who commit professional violations in Indonesia, and how lawyers sanctioned for violating the Code of Ethics can challenge. Lawyers are protected by laws, statutes, and codes of ethics in the practice of their profession. The lawyer's code of ethics is the application of assigned duties that must be consistent with the integrated criminal justice system by demanding moral accountability to the client and to God (violation of oath of office, malicious Prohibition of conduct, corruption)1. If an attorney violates the Violations section of the Code of Ethics, the case will be reviewed and heard by the Honorary Council. Keywords: Application; Code of Conduct Sanctions; Advocates